Capital Inflows and Real Exchange Rate Appreciation in Latin America : The Role of External Factors - Leiderman, Leonardo (IMF Working Papers; Working Paper, 1992)
The characteristics of recent capital inflows into Latin America are discussed. It is argued that these inflows are partly explained by conditions outside the region, like recession in the United States and lower international interest rates. This suggests the possibility that a reversal of those conditions may lead to a future capital outflow, increasing the macroeconomic vulnerability of Latin American economies. Policy options are argued to be limited.